The expression of object location with perlative preposition PER in Lithuanian - Mikulskas, Rolandas (Lietuvių kalba, 2016)
It is not unusual for a language to have one or several prepositions of originally perlative meaning that in certain pragmatic and syntactic contexts can designate location of some object (the trajector) on the other side of another, typically topographical, object (the landmark). In English such prepositions are across, through and over. In Lithuanian their sole counterpart is the preposition per. In Cognitive Grammar the cases when motion verbs or prepositions that presuppose motion are applied to designate static spatial relations between two objects are accounted for by using the notion of ‘subjective motion’ which, in its turn, is based on the notion of ‘subjectification’ (Langacker 2000, 2002, 2006). In other words, the subjective motion is defined as a cognitive operation in the course of which the conceptualizer mentally scans through the route that is presupposed by applying a motion verb or a perlative preposition. Thus the use of the lexemes of originally dynamic meaning is motivated for the designation of static spatial situations.The cases of the semantic extension mentioned above until now pose no problems for Lithuanian linguists, either lexicographers or grammarians. Thus the phenomenon of ‘locative’ use of the perlative preposition per in Lithuanian remains unidentified in dictionaries, and undescribed in grammars. No surprise, such uses of the preposition per are unattested in the Corpus of Contemporary Lithuanian, though in spoken everyday language and in the internet sources they are well attested. One may adduce structural and semantic arguments that the locative meaning ‘on the other side of’ of the perlative preposition under discussion is represented in the mental lexicon of the Lithuanian speaker and, thus, must be discerned as separate sense in dictionaries. To say more, without this sense unbridged semantic gap remains between the primary sense ‘through’ of the preposition per, representing ‘proto-scene’, and its derived senses of ‘distance’, ‘span of the time’, ‘more than’ and others − the fact of most relevance for the one who attempts to reconstruct the motivated semantic network (Tyler & Evans 2003) of this preposition.The main concern of the article, though, is not lexicography, but similarities and differences between locative usage of originally perlative construction [per + NPacc] and inherently locative constructions [kitapus + NPgen] and [anapus + NPgen]. On the first look these constructions seem synonymous: they have the same meaning ‘on the other side of’ and are mainly used in locative vs. existential sentences. But the deeper insight into the data collected from the internet sources shows that what distinguishes the first construction from the other two is the additional functional component of the ‘trajector control’ in its meaning: the construction [per + NPacc] is predominantly selected in the situations when it is relevant to the speaker not only to say that the object pointed at is on the other side of some topographical object and exactly in front of the viewer but it is within potential reach of this viewer as well. On the other hand, the construction [kitapus + NPgen] and [anapus + NPgen] is selected in the situations when the proximity of the dislocated object is not relevant to the speaker. Thus, in terms of distribution, the construction [per + NPacc], in its locative usage, with respect to its inherently locative counterparts represents the (functionally) marked case in Lithuanian.
Keywords: perlative preposition; subjective motion; subjectification; locative constructions